Water‐Soluble Gold–N‐Heterocyclic Carbene Complexes for the Catalytic Homogeneous Acid‐ and Silver‐Free Hydration of Hydrophilic Alkynes. Issue 18 (9th December 2015) - Ibrahim, Houssein; de Frémont, Pierre; Braunstein, Pierre; Théry, Vincent; Nauton, Lionel; Cisnetti, Federico; Gautier, Arnaud
Abstract: Water‐soluble gold(III/I) N‐heterocylic carbene complexes behave as efficient catalysts for the hydration of terminal alkynes in neat water. The transformation proceeds in the absence of Brønsted acids or halide scavengers and is suitable for sensitive substrates. Kinetic profiles and DFT studies provide a clear picture of intermediates present during catalysis. Abstract :